Stress Level of Nursing Students During Online Learning During the Covid-19 Pandemic - Nyumirah, Sri (STIKep PPNI Jawa Barat, 2022)
Aims: All students and educators who implement the learning process require time for the adaptation process in its application. Learning is mandatory for all institutions during the Covid-19 pandemic, despite the many obstacles that occur. The implementation of online learning in fact makes students stressed because students have to carry out an adaptation process including the technology obtained is still not optimal, network conditions are unstable, spending to facilitate learning is increasing, so that psychological problems arise. Objective: to analyze the stress level of nursing students during online learning during the Covid-19 pandemic at the Pasar Rebo Nursing Academy. Methods: quantitative descriptive. Research with a total sampling of 140 samples but 2 people refused because they were not willing to fill out the questionnaire Results: The results showed that most of the female respondents (84.8%), with an average age (20 years: 28.98%) with a high level of stress experienced by students experienced moderate stress (86.95%). Conclusion: Nursing students who carried out online learning during the Covid-19 pandemic at the Pasar Rebo Nursing Academy, mostly experienced moderate stress as many as 120 students, 17 students experienced mild stress and 1 student experienced severe stress.